The innovation of stingless bee packaging / Muhammad Firdaus Al-amin Abdullah ... [et.al.] - Abdullah, Abdullah; Omar, Mastura; Rosnan, Shalida; Zainuddin, Aezzaddin Aisyah; Shamsuddin, Nik Atilla Atasha (Universiti Teknologi MARA, Kedah, 2023)
Today's entrepreneurs produce a wide range of items, but many of them do not focus on glass products because the latter are prone to breaking in the absence of a packaging box. With the aid of this packaging box, accidents like items shattering when they fall and harming the public can be avoided. It is designed to create a packaging box in order to protect the product. appropriate packaging that is protected from anything that could damage the goods. Also, the packaging is a source of information, and Augmented Reality (AR) is used on the box to attract clients and persuade them to acquire the products. The study's conclusions have provided information about the product that needs to be sketched and regarding its construction, knowledge is required. As a result, it can create a packaging box that is very helpful to business owners and, if it is marketed, it accomplishes the necessary goals. Suggestion, The packaging box can inform customers and draw their attention by transferring knowledge to them.